2020
DOI: 10.3390/nu12061826
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and the Emotional Well-Being of Students of the Campus of Melilla (University of Granada)

Abstract: A certain link exists between the consumption of particular groups of food and well-being. In this study, we analyzed in depth the relationship between strict adherence to the Mediterranean diet (MD) and emotional well-being through a descriptive, exploratory, transversal, and correlational study of students from the Campus of Melilla, University of Granada, Spain. The sample consisted of 272 individuals. Adherence to the MD was measured with the PREvención con DIetaMEDiterránea (PREDIMED) questionnaire, emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 62 publications
4
33
1
4
Order By: Relevance
“…Similar findings can be observed in the study by Chacón-Cuberos et al [46] showing how women have a better diet in relation to men. The current research shows how women adhere better to MD even though they have lower PA than men [47,48]. In contrast, similar studies [49,50] found a positive relationship between adherence to MD and PA with no differences observed between men and women.…”
Section: Discussioncontrasting
confidence: 42%
“…Similar findings can be observed in the study by Chacón-Cuberos et al [46] showing how women have a better diet in relation to men. The current research shows how women adhere better to MD even though they have lower PA than men [47,48]. In contrast, similar studies [49,50] found a positive relationship between adherence to MD and PA with no differences observed between men and women.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous work on this area suggests the association between AMD and quality of life and others the relationship between AMD and the wellbeing of Spanish college students [76]. Positive associations between AMD adherence and higher levels of subjective happiness have been found in adolescents [77].…”
Section: Discussionmentioning
confidence: 93%
“…Emotional distress causes a preference and craving for carbohydrate-rich foods, and these may have a positive reinforcing effect on mood, explaining the higher PANAS positive score. However, legumes consumption has been previously related to lower stress levels and better positive affects [61]. Finally, although negative affect (PANAS negative scores) have been associated with a reduction in Factor 3 (i.e., high-fat meat and milk-derivatives) and an increase in Factor 6 (i.e., fish), research relating meat consumption with mood and life quality is inconclusive, with contrasting results; so, more research is needed to investigate these relationships [61].…”
Section: Effect Of Mood On Nutritionmentioning
confidence: 99%
“…However, legumes consumption has been previously related to lower stress levels and better positive affects [61]. Finally, although negative affect (PANAS negative scores) have been associated with a reduction in Factor 3 (i.e., high-fat meat and milk-derivatives) and an increase in Factor 6 (i.e., fish), research relating meat consumption with mood and life quality is inconclusive, with contrasting results; so, more research is needed to investigate these relationships [61]. However, it might be suggested that this effect depends on a subgroup of people with modest depression preferring a diet with fish and less high-fat meat and milk-derivatives as a strategy to deal with their symptoms.…”
Section: Effect Of Mood On Nutritionmentioning
confidence: 99%